Responsive structures in multinational organizations : engaging employee knowledge across diverse contexts - Andersen, Torben Juul; Jakobsen, Michael (Emerald studies in global strategic responsiveness., 2026)
Multinational organizations are faced with ongoing shifts in socio-economic conditions and cultural demands in diverse market contexts. Adapting to these changing conditions will require a balance between hierarchical and networked structures that enable integration of autonomous and inclusive modes of local business activities. From this vantage point, we explore central aspects of empathy and mindfulness as the means to accommodate different assumptions between headquarter managers and employees dispersed across host countries with diverse cultural norms and values. Chapters are presented here from around the world exploring operational management, the global-local nexus, tacit knowledge in MNCs, corporate culture, employee mindfulness and setting out a future pathway for developing effective MNC structures. Emerald Studies in Global Strategic Responsiveness aspires to disseminate new inspiring research insights as a potential catalyst for the development of effective approaches to deal with the exposures imposed by dynamic complexities in the global business environment. The implied organizational and societal challenges require effective responses from both public and private organizations induced by supportive policy initiatives. The associated challenges are beyond the control of executive powers and exceed the capacity of single institutions thus underpinning a call for collaborative approaches and collective actions to foster viable solutions for a sustainable future.